The study of lipid profile and other cardiovascular risk factors in children born to parents having premature ischemic heart disease - R., Savitha M.; Krishnappa, Santhosh; Jayaram, Shubha (International Journal of Contemporary Pediatrics, 2019)
Background: Most of the studies on cardiovascular risk factors are concentrated on adults. But atherosclerotic process begins in childhood and is influenced by genetics, diet and life style. Hence, present study was undertaken. The objectives of the study were to study lipid profile and other cardiovascular risk factors like hypertensive status, BMI(Body mass index) in children aged between 5years and 18 years born to parents having premature IHD(Ischemic heart disease), to study diet and life style factors in study group having family history of IHD, to study the sociodemographic profile of dyslipidemia. Methods: A 200 Cases of premature IHD were selected. Their children(n=200) in the age group of 5 to 18 years were selected and analysed for cardiovascular risk factors. They were compared with 200 normal children without any family history of IHD. Results: On comparison of mean lipid profile between cases and controls HDL cholesterol was very low amongst cases (p=0.001). The mean values of triglycerides and VLDL were very high amongst cases (p=0.001). The mean atherogenic index (AI) was high amongst cases (p=0.001). Prehypertension or hypertension was seen amongst 8.5% cases (p=0.004). Amongst the cases 19.5% had excess junk food intake (p=0.001). 51.5% of cases had sedentary life style (p=0.001). Conclusions: Children in our area born to parents with premature IHD have significant incidence of dyslipidaemia. There is an increased incidence of other cardiovascular risk factors like hypertension, excess junk food intake, sedentary life style in these children.